Beyond Unreliable: How Snitches Contribute to Wrongful Convictions - Natapoff, Alexandra (2010)
This Comment briefly surveys in Part I some of the data on snitch-generated wrongful convictions. In Part II, it describes in more detail the institutional relationships among snitches, police, and prosecutors that make snitch falsehoods so pervasive and difficult to discern using the traditional tools of the adversarial process. Part III concludes with a litigation suggestion for a judicial check on the use of informant witnesses, namely, a Daubert-style pre-trial reliability hearing. The Appendix in Part IV contains a sample motion requesting and justifying such a hearing